Soil use conflict and critical enviromental areas in the marine zone of Lima - Ayala Gutiérrez, Máximo (2007)
The coastal – marine zone of the Metropolitan area of Lima-Callao (ZCMLC), is an environmental unit composed by two ecosystems: coastal and marine with biological, economical and cultural significance. However in recent years, it has been suffering problems caused by the inadequate use of soil caused by urban growth, environmental degradation and the neglect of the authorities who are responsible for the administration. To face this problem, some goals were raised such as the establishment of delimitation of the coastal - marine zone of the Metropolitan area of Lima - Callao, the identification of areas that present conflicts of land use and the identification of environmental critical areas. The ZCMLC, represents about 117648 ha, coastal and marine area included, where five environmental units were identified: Ancon-Santa Rosa (16108.87 hectares.); Ventanilla-Callao (38657.01 hectares.); La Perla-Barranco (25803.96 hectares.); Chorrillos-Lurin (16726.08 hectares.) and Punta Hermosa-Pucusana (20352.23 hectares). About 4,924.83 ha presented land use conflicts, which represent 12% of the area considered as an area of the coastal ZCMLC. These conflicts were identified largely within the environmental units of Chorrillos-Lurin and Ventanilla-La Punta. There was also identified eight environmental critical areas, caused mainly by urban encroachment in the coastal strip, loss of free access to beaches, pollution of sea waters, beaches and rivers, lack of green areas, loss of recreational areas, loss of coastal species, loss of natural landscape, among others.